Captain America. Vol. 2, Trying to come home - Straczynski, J. Michael, 1954- (Marvel Worldwide, Inc., a subsidiary of Marvel Entertainment, LLC, 2024)
"New information about Captain America's recent attacker--a mysterious figure known only as the Emissary--has Steve Rogers, Misty Knight and Sharon Carter scrambling to protect a peace rally from being this new foe's next target. But how can masters of physical and mental might defend against the supernatural prowess of an ancient evil? Get ready for a fight to the death as Cap races to take down the Emissary before he strikes again! Will an assist from Doctor Strange be enough to turn the tide? Plus: Steve Rogers meets a strange new ally named Lyla, guardian of the mysterious Front Door Cabaret!"--